Immunogenicity of a quadrivalent human papillomavirus vaccine in pediatric kidney and liver transplant recipients. (5th February 2023) - Kitano, Taito; Schwartz, Kevin L.; Abdulnoor, Mariana; Garfield, Hartley; Booran, Nasser Khodai; Avitzur, Yaron; Teoh, Chia Wei; Hébert, Diane; Allen, Upton
Abstract: Background: Solid‐organ transplant recipients are at increased risk of developing human papillomavirus‐related diseases. Methods: To evaluate the immunogenicity of a quadrivalent vaccine, a prospective observational study included females aged 12–19 years who had received kidney or liver transplants, or were otherwise healthy volunteers. With the three‐dose vaccination, serum antibodies were measured. Results: The study included 17 transplant recipients (seven kidney and 10 liver) and 16 healthy participants. Six of seven kidney transplant recipients were on three immunosuppressive medications, whereas 9 of the 10 liver transplant recipients were on one. For the serology within 6 months from the last vaccine dose, the geometric mean titers of human papillomavirus types 6, 11, 16, and 18 were 26.7, 8.6, 35.7, and 42.4 (kidney transplant); 579.2, 569.3, 3097.3, and 835.7 (liver transplant); and 860.5, 638.8, 4391.6, and 902.6 milli‐Merck Units/ml (healthy). The seropositivity rates of kidney transplant recipients for the four serotypes ranged from 50% to 75%, while all liver transplant recipients and healthy participants had 100% seropositivity rates for all four types. While there were no statistical differences of titers between liver transplant recipients and healthy participants, the titers of kidney transplant recipients were lower than those of healthy participants for type 6 ( p  = .034), type 11 ( p  = .032), and type 16 ( p  = .032). Conclusions: The results support the recommendation of human papillomavirus vaccination in pediatric transplant recipients given the significant risk of human papillomavirus‐related diseases in this population, though immunogenicity was lower in kidney transplant recipients on multiple immunosuppressive medications.